A method of designing of torque-flow pump impeller with curvilinear blade profile - Kondus, Vladyslav; Kalinichenko, Pavlo; Gusak, Olexandr (Eastern-European Journal of Enterprise Technologies, 2018)
The research is devoted to energy efficiency increasing of a “Turo” type torque-flow pump by improving its impeller. This allows minimizing the total pump installation life cycle cost as a result of reducing the costs of electricity. The application of the real fluid flow physical model in a torque-flow pump allowed developing the energy distribution mathematical model in its flowing part. In the proposed mathematical model, the ratio of component flows was defined. These include the toroidal vortex, the flow coming from the impeller intervane channels directly to the outlet (through-flow), and the flow that does not contact with the blades (flowing stream). As a result, it is found that the maximum possible energy efficiency of the torque-flow pump operating process without taking into account hydraulic losses is ηop=0.67. The method of designing the torque-flow pump impeller with a curvilinear blade profile is developed. The method is based on the proposed mathematical model of energy distribution in the torque-flow pump flowing part. The blade inlet angle β1 and the angle on the calculated impeller radius βr are proposed to be carried out in accordance with the fluid flow in the impeller intervane channels. The radius r<r2 is chosen for which there is a radial motion of the fluid in the intervane channels of the impeller. The numerical investigation made it possible to estimate the fluid flow structure in the torque-flow pump flowing part. Using the proposed impeller has minimized losses at the inlet and in its intervane channels as a result of coordination of the fluid flow and the impeller skeleton geometry. Increasing the blade part and reducing the vortex part of the operating process allowed increasing the energy efficiency of the torque-flow pump. The proposed geometry of the impeller allows increasing the energy efficiency of existing torque-flow pumps by 4–5 %.